Search
Ask a question
0

How to simplify each expression & write in scientific notation?

(3*10^6) (2*10^4)

(7*10^5)^3

(6*10^-3)^3(2*10^-4)

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Tamara J. | Math Tutoring - Algebra and Calculus (all levels)Math Tutoring - Algebra and Calculus (al...
4.9 4.9 (51 lesson ratings) (51)
0

First note that since multiplication is commutative, you can the order of the numbers being multiplied without altering the final result. Also, by the associative property, the grouping of the numbers being multiplied can also be changed.

1.)    (3 · 106)(2 · 104)     ==>     (3 · 2)(10· 104)

When multiplying exponents with like bases, you keep the same base and add the exponents.

     (3 · 2)(10· 104) = (6)(106+4) = (6)(1010) = 6 · 1010

2.)     (7 · 105)3    

           ==>     (7 · 105)(7 · 105)(7 · 105= (7 · 7 · 7)(10· 10· 105)

                        = (343)(105+5+5) = (343)(1015

                        = 343 · 1015 = 3.43 · 1017 

     OR

          (7 · 105)3  =  (7)3 · (105)3  

                          =  (73) · (105·3)  =  (343) · (1015)  =  3.43 · 1017

3.)     (6 · 10-3)3(2 · 10-4)

          ==>   (6 · 10-3)3  =  (6)3 · (10-3)3  =  (63) · (10-3·3)  

                                     =  (216) · (10-9)  =  2.16 · 10-7

         (6 · 10-3)3(2 · 10-4)  

         ==>    (2.16 · 10-7)(2 · 10-4)  =  (2.16 · 2)(10-7 · 10-4)  

                       =  (4.32)(10-7+(-4))  =  (4.32)(10-11)  =  4.32 · 10-11